Optimal placement of sensors on buildings subjected to intermediate storey excitation according to QN control method. - Xing, Liping (Earthquake engineering & structural dynamics.)
An algorithm to calculate direct velocity feedback gain with limited number of sensors is developed in a simple way such that a certain performance index is minimized according to QN control method. If a limited number of velocity outputs can be measured, full velocity responses of the whole structure can be interpolated based on the mode shapes. By defining the performance index function as a combination of the structure's velocity responses and control forces only, feedback gain can be determined according to QN control method with the external excitation being taken into account throughout the entire algorithm. Control forces are then regulated by the time invariant feedback gain matrix. The effective location of the active control devices for a building structure subjected to intermediate storey excitation has been determined to be in the three floors adjacent to the vibration source. Hence for the purpose of this paper, only the optimal placement of sensors is verified. It is shown in this paper that if the dynamic behaviour of the structure is well described by a mathematical model, sufficient response reduction effect can be achieved according to the new DVFC algorithm, and the degradation of control performance due to time delay can also be verified.